Influence of chloride solutions on the leaching of heavy metals from cement hydrates. (16th May 2023) - Zhou, Shaojun; Ogawa, Yuko; Kawai, Kenji
Highlights: Contact with CaCl2 solution greatly reduces the adsorption capacity of CSH for Pb. For MgCl2 solution, most portlandite in mortars was decomposed to form brucite. The lower the adsorbability of Pb on CSH, the larger the Pb leaching amounts. The amount of Pb leaching in CaCl2 solution is three times larger than that in other solutions. Large leachate quantity for CaCl2 solution was not caused by pore structure alterations. Abstract: This study investigates how chloride-based salts affect the immobilization and leaching of Cu, Zn, and Pb from cement hydrates and analyzes the associated internal changes in crystalline phase. Results showed that the amount of Pb leached is highest in mortar when it contacts with CaCl2 solution. A key reason for this outcome is that calcium silicate hydrate (CSH) has the lowest Pb adsorption in CaCl2 solution. Exposure to MgCl2 solution resulted in the decomposition of most portlandite to form brucite in mortars, lowering the pH to ∼9. This caused the lowest leaching rate of Cu, Zn, and Pb in MgCl2 solution.